The influence of CYP3A gene polymorphisms on cyclosporine dose requirement in renal allograft recipients - Eng, H.S.; Mohamed, Z.; Calne, R.; Lang, C.C.; Mohd, M.A.; Seet, W.T.; Tan, S.Y. (2006)
Cyclosporine is a substrate of cytochrome P-450 3A (CYP3A) subfamily of enzymes and characterized by a narrow therapeutic range with wide interindividual variation in pharmacokinetics. A few single-nucleotide polymorphisms detected in CYP3A genes have been shown to correlate significantly with the CYP3A protein expression and activity. We therefore postulated that these polymorphisms could be responsible for some of the interindividual variation in cyclosporine pharmacokinetics. The objective of our study is to determine correlation if any between single-nucleotide polymorphisms of CYP3A5 and CYP3AP1 on cyclosporine dose requirement and concentration-to-dose ratio in renal allograft recipients. Cyclosporine-dependent renal allograft recipients were genotyped for CYP3A5 A6986G and CYP3AP1 G-44A. The cyclosporine dosages prescribed and the corresponding cyclosporine trough levels for each patient were recorded so that cyclosporine dose per weight (mg/kg/day) and concentration-to-dose ratio (C 0/D, whereby C 0 is trough level and D is daily dose per weight) could be calculated. A total of 67 patients were recruited for our study. The dose requirement for 1, 3, and 6 months post-transplantation ranged 2.3-11.4, 1.0-9.0, and 1.4-7.2 mg/kg/day, respectively. Patients with *1*1*1*1 (n = 5) CYP3A5- and CYP3AP1-linked genotypes needed higher dose of cyclosporine compared to patients with *1*3*1*3 (n = 27) and *3* 3*3*3 (n = 33) linked genotypes in months 3 and 6 post-transplantation (P < 0.016). The identification of patients with *1*1* 1*1 by CYP3A5 and CYP3AP1 genotyping may have a clinically significant and positive impact on patient outcome with reduced rejection rate by providing pretransplant pharmacogenetic information for optimization of cyclosporine A dosing. Â© 2006 International Society of Nephrology.